'Active Families': Familization, Housing and Welfare across Generations in East Asia. (10th October 2012) - Izuhara, Misa; Forrest, Ray
Abstract: Debates around welfare change have tended to concentrate on the balance between market and state provision. Although there is increasing reference to a mixed economy of welfare, this generally signifies a greater emphasis on a third sector of voluntary/community level provision. However, the family sphere has been, and still remains, an important and dynamic source of welfare provision across changing regimes and between generations. With this as background, the article addresses three particular questions. First, how has the role of families in the welfare mix changed over time? Second, how do family 'strategies' adapt to structural changes in order to maximize collective/individual benefits in certain areas and how do these strategies evolve over generations? Third, is such family engagement in welfare influenced by policy shifts appropriately conceptualized as 're‐familization' or 'de‐familization'? These issues are explored in the comparative socio‐economic and cultural contexts of China and Japan and draw on qualitative research with three generations of families in Shanghai and Tokyo.